Digitalization of the Educational Environment: Risk Assessment of Distance Education by Russian and Vietnamese Students - A. V. Noskova; D. V. Goloukhova; A. S. Proskurina; T. H. Nguen (Высшее образование в России)
The digitalization of higher education is a long-term trend that gained a new impetus for further development because of the forced transition to distance learning during the COVID-19 pandemic. The aim of the article is to analyze the impact of digital transformation on the educational process in universities and to describe the risks through the students’ eyes. The analysis is based on the results of a survey conducted by the authors in 2020 among students of two universities - Moscow State Institute of International Relations (MGIMO) and the Institute of the Trade Union Movement of the General Confederation of Labor of Vietnam (IPLV).The article describes the methodology of the online survey. The attitude towards distance learning is interpreted as a three-level attitude with emotional, cognitive and behavioral aspects. It is suggested that students’ readiness to switch to distance learning is determined by a set of macro and micro factors. Among the macro factors are the national specifics of the educational system, traditions in the field of higher education, infrastructure, the national educational policy, and the mobilization potential of the population. Among the micro factors are the cognitive and other psychological characteristics of the students, the socio-psychological openness to innovation.According to the survey results, there is certain similarity in the way Russian and Vietnamese students assess their experience of distance learning. At the same time, significant differences in the perception of the outcome of the digital transformation of education have been revealed. For MGIMO students, major risks are associated with dehumanization, the severing of social ties, and the possible loss of student status. For Vietnamese students the most significant risks are mainly associated with the fears of the decreasing quality of education. It is therefore concluded that distance learning is both the field of opportunities and possible source of individual and institutional risks.